Seasonal variation of suspended sediment and its relationship with turbidity in Cam - Nam Trieu estuary, Hai Phong (Vietnam) - Nguyen , Minh Hai; Ouillon, Sylvain; Vu, Duy Vinh (Vietnam Journal of Marine Science and Technology, 2021)
We analyzed the seasonal variation of suspended sediment and its relationship with Turbidity in Cam - Nam Trieu estuary based on data measured during three different seasons: Early wet season (May 2015), wet season (September 2015) and dry season (January 2016). The results highlighted the seasonal variation of suspended particle matter (SPM) concentrations with river flow. The average SPM concentration was highest during the dry season, with 62.95 mg/L. They were not significantly different between the early wet and wet seasons, with 59.65 mg/L and 50.94 mg/L, respectively. This study also demonstrated a strong dependence between SPM and Turbidity in the study area. The coefficients of determination varied from 0.867 to 0.971 (linear relationship), and from 0.95 to 0.991 (proportional relationship). Therefore, turbidity can be used to estimate SPM concentration. However, this relationship changed markedly with the seasons, and hence when determining SPM concentration, seasonal factors must be considered.